2007
DOI: 10.1159/000100981
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Induced Alteration of Glucose Homeostasis in the Rat: The Contribution of Hypothalamic-Pituitary-Adrenal Axis Activation

Abstract: Background/Aims: To our knowledge, a suitable animal model to investigate how atypical antipsychotics may induce diabetes in patients has not received much attention. Methods: We investigated the effects of acute as well as subchronic administration of clozapine on food intake, body weight gain, glucose tolerance and insulin secretion in response to glucose in Sprague-Dawley rats. We then evaluated the effects of clozapine on corticosterone secretion and 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 77 publications
(58 reference statements)
3
40
0
Order By: Relevance
“…SGAs are a widely used class of drug, but one side effect of these drugs is the development of a type 2 diabetes-like phenotype characterised by high circulating blood glucose and insulin, especially with clozapine and olanzapine [2,6,9,10,22]. In humans, as the use of SGAs is associated with weight gain, the assumption has been made that these drugs are causing the development of severe insulin resistance in the major insulin-sensitive tissues, inducing compensatory increases in insulin secretion [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGAs are a widely used class of drug, but one side effect of these drugs is the development of a type 2 diabetes-like phenotype characterised by high circulating blood glucose and insulin, especially with clozapine and olanzapine [2,6,9,10,22]. In humans, as the use of SGAs is associated with weight gain, the assumption has been made that these drugs are causing the development of severe insulin resistance in the major insulin-sensitive tissues, inducing compensatory increases in insulin secretion [3].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed a slight increase in blood glucose level after clozapine treatment but the glucose measurements were obtained from anaesthetised rats, limiting the interpretation of the results [9]. Similarly, another group investigated the effect of clozapine on glucose tolerance, but used trunk blood following decapitation, which in itself is normally associated with elevated blood glucose concentrations [10]. Researchers have also reported that olanzapine caused insulin resistance in L6 skeletal muscle cells, but this effect is only apparent using a 100-fold (100 µmol/l) higher concentration of the drug than we would see in the clinical setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since 5-HT causes a rapid stimulation in glucose uptake in both L6 myotubes and C2C12 myoblasts through 5-HT 2A activation (Hajduch et al 1999;Tulipano et al, 2007), we hypothesized that the stimulatory effect of olanzapine on glucose uptake would depend on a partial agonist activity at We have previously shown that the addition of 20 µM clozapine to growth medium supplemented with HS, for 48 hours post-differentiation, does not significantly change the final width of C2C12 myotubes as documented by staining with Giemsa and microscope analysis (Tulipano et al, 2007).…”
Section: Effects Of Olanzapine On Basal-and Insulin-stimulated Glucosmentioning
confidence: 99%
“…Conversely, a significant increase of glucose uptake into isolated muscles from rats treated with olanzapine in vivo and subsequently incubated with 10 µM olanzapine in vitro, was shown (Houseknecht et al, 2007). In murine skeletal muscle cell (C2C12) cultures, clozapine did not inhibit basal and insulin-induced glucose transport but it was able to antagonize the stimulatory effect of -methyl-5-hydroxytryptamine, a 5-HT 2A agonist, on glucose uptake (Tulipano et al, 2007). Finally, 100 µM olanzapine impaired glycogen synthesis via inhibition of the classical insulin-signaling cascade in L6 skeletal muscle cells; the effect of olanzapine on glucose internalization was not studied in these cells (Engl et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation